How can African agriculture adapt to climate change: Climate Change Impacts in Ethiopia: Hydro-Economic Modeling Projections - You, Gene Jiing-Yun; Ringler, Claudia (International Food Policy Research Institute, 2011)
Two factors critical to assuring food security, whether at the local or the global level, are increasing crop productivity and increasing access to sustainable water supplies. These factors are also vital to the economic success of agriculture, which is particularly important in Ethiopia given that the sector accounts for about 41 percent of the country's gross domestic product (GDP), produces 80 percent of its exports, employs 80 percent of the labor force, and is a major source of income and subsistence for the nation's poor.